TECHNOLOGY OF USING LOCAL MATERIALS WHEN CREATING DECORATIVE VASES IN THE ART OF POTTERY. - Buvayev Vakhobjon Sadikovich (The latest pedagogical and psychological innovations in education, 2025)
this article The art of pottery is one of the most ancient and rich craft directions of human culture. Through it, not only practical objects were created for everyday life, but also specific images of national culture and art were expressed. In particular, the creation of decorative vases has its unique place in pottery, through which artisans have shown their aesthetic vision, natural love and national identity. In this process, local raw materials are of great importance, in particular, clays present in different regions.